Environment as a Resource, not a Constraint - Blaž Remic (Journal of Contextual Economics – Schmollers Jahrbuch, 2021)
In this article I argue that the study of contextual issues in economics has been limited in its scope because economists have mostly conceived of the environment as a constraint on individual action. I identify and discuss three conventions that pull economists into such conceptualization of the environment. For each of the three I provide ways forward for contextual economics to avoid the pull. I then employ insights from the recent cognitive science on socially extended mind to demonstrate how the project of contextual economics as envisioned in this article can benefit from reconceptualizing the environment not as a constraint on individual action but as a resource for constituting socially extended cognitive processes. Rather than being simply about gathering more and better data, contextual economics can offer a powerful approach for studying social world based on entangled interactions between individual actors and their environments.
Keywords: B59; D02; D91; Z13; B41; B53; 330; Socially Extended Mind; Scientific Integration; Contextual Economics; Behavioral Economics; Methodology; Cognitive Institutions